Targeted and high-throughput gene knockdown in diverse bacteria using synthetic sRNAs - Jae Sung Cho; Dongsoo Yang; Cindy Pricilia Surya Prabowo; Mohammad Rifqi Ghiffary; Taehee Han; Kyeong Rok Choi; Cheon Woo Moon; Hengrui Zhou; Jae Yong Ryu; Hyun Uk Kim; Sang Yup Lee (Nature Communications, 2023)
Abstract Synthetic sRNAs allow knockdown of target genes at translational level, but have been restricted to a limited number of bacteria. Here, we report the development of a broad-host-range synthetic sRNA (BHR-sRNA) platform employing the RoxS scaffold and the Hfq chaperone from Bacillus subtilis. BHR-sRNA is tested in 16 bacterial species including commensal, probiotic, pathogenic, and industrial bacteria, with >50% of target gene knockdown achieved in 12 bacterial species. For medical applications, virulence factors in Staphylococcus epidermidis and Klebsiella pneumoniae are knocked down to mitigate their virulence-associated phenotypes. For metabolic engineering applications, high performance Corynebacterium glutamicum strains capable of producing valerolactam (bulk chemical) and methyl anthranilate (fine chemical) are developed by combinatorial knockdown of target genes. A genome-scale sRNA library covering 2959 C. glutamicum genes is constructed for high-throughput colorimetric screening of indigoidine (natural colorant) overproducers. The BHR-sRNA platform will expedite engineering of diverse bacteria of both industrial and medical interest.